Mitigating mode instabilities by controllable mode beating excitation with a photonic lantern - Lu, Yao; Jiang, Zongfu; Xiao, Hu; Chen, Zilun; Jiang, Man; Chai, Junyu; Yang, Hao; Ding, Lianchuang; Zhang, Dan; Zhang, Jiangbin; Zhou, Qiong; Liu, Wenguang (Frontiers in Physics, 2023)
In this study, a method of stabilizing the output beam of a large-mode-area fiber amplifier operating above the mode instability threshold is demonstrated. A mode control system based on the photonic lantern is used to excite dynamic mode beatings as the seeding stage of a 42/250 µm Yb-doped fiber amplifier. We propose a theoretical explanation for the validity of this method: provided that the mode interference patterns generated by input mode beatings are antisymmetric to those in the main amplifier caused by thermally induced non-linear effects, the refractive index grating will not be formed to indicate the onset of mode instability. Experimentally, significant mode stability and beam quality improvement have been achieved in this system at power levels of up to nearly four times the mode instabilities threshold.